Life‐history diversity and its importance to population stability and persistence of a migratory fish: steelhead in two large North American watersheds. (24th March 2014) - Moore, Jonathan W.; Yeakel, Justin D.; Peard, Dean; Lough, Jeff; Beere, Mark; Genner, Martin
Summary Life‐history strategies can buffer individuals and populations from environmental variability. For instance, it is possible that asynchronous dynamics among different life histories can stabilize populations through portfolio effects. Here, we examine life‐history diversity and its importance to stability for an iconic migratory fish species. In particular, we examined steelhead (Oncorhynchus mykiss), an anadromous and iteroparous salmonid, in two large, relatively pristine, watersheds, the Skeena and Nass, in north‐western British Columbia, Canada. We synthesized life‐history information derived from scales collected from adult steelhead (N = 7227) in these watersheds across a decade. These migratory fishes expressed 36 different manifestations of the anadromous life‐history strategy, with 16 different combinations of freshwater and marine ages, 7·6% of fish performing multiple spawning migrations, and up to a maximum of four spawning migrations per lifetime. Furthermore, in the Nass watershed, various life histories were differently prevalent through time – three different life histories were the most prevalent in a given year, and no life history ever represented more than 45% of the population. These asynchronous dynamics among life histories decreased the variability of numerical abundance and biomass of the aggregated population so that it was > 20% more stable than the stability of the weighted average of specific life histories: evidence of a substantial portfolio effect. Year of ocean entry was a key driver of dynamics; the median correlation coefficient of abundance of life histories that entered the ocean the same year was 2·5 times higher than the median pairwise coefficient of life histories that entered the ocean at different times. Simulations illustrated how different elements of life‐history diversity contribute to stability and persistence of populations. This study provides evidence that life‐history diversity can dampen fluctuations in population abundances and biomass via portfolio effects. Conserving genetic integrity and habitat diversity in these and other large watersheds can enable a diversity of life histories that increases population and biomass stability in the face of environmental variability.